Hubungan Tone Pengungkapan, Profitabilitas, Likuiditas, Struktur Modal, dan Ukuran Perusahaan terhadap Nilai Perusahaan - Christella Jeaneva Eugenia; Eugenia Vanessa Rimba; Saarce Elsye Hatane; Oviliani Yenty Yuliana (Business Accounting Review, 2020)
Firm’s annual report is a significant factor for investors in making an investment decision in the capital market. Information disclosure becomes a signal to inform investors about the firm’s future prospects that can affect the firm value. Not only financial information, such as profitability, liquidity, capital structure and firm size, non-financial information is also become an important factor that affects firm value. Therefore, sentiment/tone in the narrative part of the annual report becomes an important tool in delivering “good” or “bad” signals to investors. The purpose of this study was to determine the relationship of tone disclosure, profitability, liquidity, capital structure, and firm size to firm value. The sample used in this study were 92 tourism and hospitality listed firms on Indonesia Stock Exchange, Stock Exchange of Thailand, Malaysia Stock Exchange, Singapore Stock Exchange, and Philippine Stock Exchange in 2015-2018 which were selected by purposive sampling method. Data analysis using multiple regression analysis. Based on the results of the analysis, this study found that tone disclosure and capital structure has a positive effect on firm value. Meanwhile profitability, liquidity, and firm size do not have a significant effect on firm value.